2000
DOI: 10.1023/a:1005439905134
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Our aim was to evaluate the relationship between gastric emptying and demographic, clinical, histological, and secretory features in patients with nonautoimmune fundic atrophic gastritis. Only 31% of 45 patients with fundic atrophic gastritis presented with achlorhydria. Scintigraphic gastric emptying of solids was delayed compared to healthy controls. Patients with achlorhydria showed gastric emptying rates lower than those with preserved acid secretion. Significant, but weak, correlations were observed betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 22 publications
1
6
1
Order By: Relevance
“…This poses the possibility that most of the previous scintigraphic studies have so far missed the initial rapid emptying elicited by gastric acid suppression. One scintigraphic study has suggested an association between altered gastric emptying and gastric hypoacidity; after ingestion of a mixed solid-liquid meal, the lag period was shorter and the subsequent emptying was slower in dyspeptic patients with achlorhydria than in those with reserved acid secretion [20]. These results support our speculation that gastric hypoacidity initially enhances and subsequently suppresses gastric emptying of solid meals.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…This poses the possibility that most of the previous scintigraphic studies have so far missed the initial rapid emptying elicited by gastric acid suppression. One scintigraphic study has suggested an association between altered gastric emptying and gastric hypoacidity; after ingestion of a mixed solid-liquid meal, the lag period was shorter and the subsequent emptying was slower in dyspeptic patients with achlorhydria than in those with reserved acid secretion [20]. These results support our speculation that gastric hypoacidity initially enhances and subsequently suppresses gastric emptying of solid meals.…”
Section: Discussionsupporting
confidence: 80%
“…Our data show that rabeprazole modestly elevated the fasting serum gastrin levels. Previous authors documented an inverse correlation between serum gastrin concentrations and rates of the post-lag gastric emptying based on a wide range of gastrin levels (up to 1,200 pg/ml), but the correlation was very weak [20]. In our study, hypergastrinemia might play a role in delaying the later (post-lag) phase of gastric emptying, but we think that this role is merely minor.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…Previously, in atrophic gastritis, a role of gastric emptying has been investigated, showing a delayed emptying both in the autoimmune [28] and nonautoimmune atrophic gastritis. [29] In addition, the reduced gastric acid secretion seems to be associated with the presence of dyspepsia [30] and more recently, a Japanese study conducted on dyspeptic outpatients showed that hypochlorhydria was significantly associated with higher dyspeptic symptom scores and dysmotility-related scores, in particular, in female. [31] …”
Section: Discussionmentioning
confidence: 99%
“…A possible source of error in permeability studies of the stomach is delayed gastric emptying. Although being a controversial issue, this has been shown to occur in patients with chronic and atrophic gastritis [22,23,24]. Another possible source of error in atrophic gastritis could be the reduced volume of gastric fluid secretion [25].…”
Section: Discussionmentioning
confidence: 99%